SPEED DEVELOPMENT METHODS FROM MARTIAL ARTS IN THE MIDDLE SCHOOL - Florian Benedek; Cristian Macovei (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
I chose this case study because I believe that the introduction of methods from martial arts world to develope speed in classes ofphysical education and sport in the 5th and 8th grade will lead to a lifting level of training and education of speed and why not a way to attract and provide a greater motivation among pupils to develop this motric quality. And I say this because I do not know how many of us noticed when we pass near to a school yard in the side, children who spend their energy in reproducing or imitating various martial arts movements seen on television or videogames. And we, as future teachers of physical education and sport can use this waste energy in a constructive manner, using them to awaken their interest.